Highly fluorescent carbon dots from wheat bran as a novel drug delivery system for bacterial inhibition - John T.S.; Yadav P.K.; Kumar D.; Singh S.K.; Hasan S.H. (My University, 2025)
In this study, we prepared carbon dots (CDs) from wheat bran via hydrothermal treatment at 180°C for 3 h. The prepared CDs showed blue-green fluorescence under UV light. The fluorescence emission study of the CDs revealed that they showed maximum fluorescence emission at 500 nm. The prepared CDs showed a high quantum yield of 33.23%. Solvent-dependent fluorescence emission analysis of the CDs was performed to study the variation in fluorescence emission characteristics with solvent polarity. The prepared CDs were conjugated with amoxicillin (AMX) to explore its potential for use as a drug delivery agent for AMX. The drug release profile of the CD–AMX conjugates was analyzed at different pH (5.0, 6.8 and 7.2) to study drug release kinetics. CD–AMX conjugates showed notable bacterial inhibition against Gram-positive (S. aureus) and Gram-negative (E. coli) strains with minimal cytotoxic effects, indicating its potential as a promising antibacterial drug delivery system. © 2020 John Wiley & Sons, Ltd.